Colloid‘s influences on microalgae growth as a potential environmental factor - 赵新淮 张正斌 刘莲生 (Chinese journal of oceanology and limnology, 2003)
The role of colloid as “colloid pump”in the ocean is well known. The important influence of colloid in seawater on the growth of microalga was found in our 1999--2000 study. Colloid concentrates were obtained by employing a cross-flow filtration system to ultrafilter seawater(which had been pre-filtrated by 0.45 μm acetate cellulose membrane) successively with different membranes. Ultrafiltration retentions (we called them colloid concentrates) together with control sample (seawater without colloid) were then inoculated with two species of microalgae and cultivated in selected conditions. Monitoring of microalgae growth during cultivation showed that all colloid concentrates had obvious influence on the growth of the microalgae studied. Addition of Fe(OH)3 colloid or organic colloid (protein or carbohydrate) to the control sample enhanced the microalgae's growth.